PEMODELAN UNTUK MEMPREDIKSI DAYA SERAP BABY DIAPERS DARI NON WOVEN BOGSANG BERDASARKAN HASIL EKSPERIMEN - Malichah Muhtarromah; Dantik Puspita Sari; Nurul Khadaryati; Ilma Fadhlia Furqanaa (Teknoin, 2015)
At this time it has been a lot of research on natural fibers were used as material for textiles. Therefore, the researchers wanted to generate natural material-based medical textile. The objectives and targets will be achieved from this research, is utilizing waste stem of banana post harvest into something more valuable as well as making modeling results done. The research results from this banana trunk fiber as material for the manufacture of baby diapers are environmentally friendly and have a high absorbent against water. This research was conducted with the experimental method to generate optimal achievement, namely by doing the processing post harvest banana stems. The first stage is looking for post harvest banana stems which are usually discarded. The next step is extracting stem of banana leaf into tow fiber, tow fiber processing became the staple through the process of relaxing, washing, cutting and opening. And the end result will be either web (non woven fiber) which will be in the laboratory test on humidity, power and fiber dimensions. Then make the modeling of laboratory test results. From the results of the experiment, the value will be in the predictions is the numeric data. This is usually made as a reference or basis for making the modeling that can predict. The prediction are more focus on the identification of trend of the distribution on the test data generated